Siri As a Tool for Speaking Practice: A Case Study of EFL Learner Interaction with Intelligent Assistants - Siddiq, Aditya Fadhilah; Sumarni, Sumarni (Journal of English Education Program, 2025)
This study explored the experience of an EFL learner, Emily, a non-native English Speaker who has utilized Apple"™s Siri since 2015 for a wide range of daily talks as a complementary language learning tool for English as a Foreign Language (EFL) learners. The data were collected through semi-structured interviews and log conversations with Siri. The findings show Emily"™s experience with Siri. The study found that Emily frequently used Siri with a wide range of utilization such as basic voice commands to aid her in writing and sending text messages, searching for learning resources, and setting her schedule. In addition, the study also revealed that Siri has facilitated Emily through its voice control abilities in providing a feedback mechanism. Emily often clarified, rephrased, or repeated the command when Siri could not understand it. Emily can see the voice control display screen on her Apple device, which provides a visual transcript of the performance flow alongside audible responses from Siri. However, the study also identified challenges associated with using Siri, such as the misunderstandings of requests due to pronunciation issues and Siri"™s limitations in handling complex requests. Overall, this research contributes valuable insights into the benefits and limitations of using general-purpose AI tools like Siri to support language learning.